Optimizing rice farming business inputs in shallow freshwater swamp (case study of Sungai Dua Village, Rambutan District, Banyuasin Regency) - Yuwinti Nearti; Muhammad Andri Zuliansyah; Nirmala Jayanti (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
One of the food crops that was widely cultivated by the community was lowland rice. Food security was a superior commodity where lowland rice was the icon. The objectives of this research was to determine the use of production factors in optimizing rice based on output effects through farming inputs and to determine production factors in the economic efficiency of rice farming. The research used production function analysis Cobb Douglas and Marginal Product Value. The production factor data analysis method used multiple regression analysis with software SPSS 25 while Marginal Product Value (NPM) used Stochastic Frontier Analysis (SFA). The results of the research showed that production factors that could influence the input of rice farming consist of fertilizer and seeds, where each time more input was used for the part needed, the farmer's income in planting period 1 was higher than planting period 2. Lowland rice farming in Sungai Dua Village, District Rambutan Banyuasin Regency in shallow swampy areas, after Marginal Product Value analysis was carried out, the planting season for both period 1 and period 2 was declared inefficient. Farming inputs that were not yet optimal in shallow swampy areas consist of fertilizer and seeds. The seeds used by Inpara 2 were suitable for swampy land but were still used excessively, while fertilizer was an increase in nutrients for the soil and plants but the use was still small due to farmers' limited capital. limited. F-hit >F- tab in each stratum with a confidence level of 95% in each stratum, it was stated that the independent variables together have a significant effect on the dependent variable. Intensification of plant maintenance was given more attention by increasing the use of labor to support increased output and maximum income.